KONSENTRASI HAMBAT MINIMUM (KHM) KADAR EKSTRAK ETANOL BATANG BAJAKAH TAMPALA (Spatholobus littoralis Hassk) TERHADAP BAKTERI ESCHERICHIA COLI MELALUI METODE SUMURAN - Mochammad Maulidie Alfiannor Saputera; Tio Widia Astuti Marpaung; Noverda Ayuchecaria (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Empirically, one of the plants that are widely used by the Dayak tribe as a medicine is the bajakah tampala (Spatholobus littoralis Hassk.) This plant is claimed to be able to treat several diseases such as abdominal pain, diarrhea and dysentery. But until now studies on the antibacterial activity of bajakah tampala have never been done. This study studied the antibacterial activity of bajakah ethanol extract against the growth of Escherichia coli bacteria and minimum inhibitory value (MIC). This type of research is experimental research. The stem bajakah Tampala looks like it wastaken from the inland forest in Garung Village, Jabiren District, Pulang Pisau Regency, Central Kalimantan. The sample of this study was 70% ethanol extract of bajakah tampala stems obtained by maceration. Extract payment of antibacterial activity using a concentration of 3.12%; 6.25%; 12.5%; 25% and 50%. The positive control used is ampicillin 0.01 mg/ml and negative control using distilled water. Tests are carried out by the well method. The tested data were analyzed statistically by the One-Way ANOVA test method. The results of the study showed that the ethanol extract bajakah tampala could inhibit the growth of E. coli bacteria. The biggest inhibition of E. coli bacteria at a concentration of 50% with an average inhibition diameter of 20.32 mm. included in the category of very strong. The minimum inhibitory concentration of extract batang bajakah tampala is 6.25%